2007
DOI: 10.2337/db06-1299
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Linkage Analyses to Identify Loci for Diabetic Retinopathy

Abstract: Hyperglycemia and long duration of diabetes are widely recognized risk factors for diabetic retinopathy, but inherited susceptibility may also play a role because retinopathy aggregates in families. A genome-wide linkage analysis was conducted in 211 sibships in which >2 siblings had diabetes and retinal photographs were available from a longitudinal study. These sibships were a subset of 322 sibships who had participated in a previous linkage study of diabetes and related traits; they comprised 607 diabetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 46 publications
2
81
0
1
Order By: Relevance
“…Two of these genes (ARHGAP22 and PLXDC2) are involved in endothelial cell angiogenesis. They also confirmed the results of a previous genomewide linkage study associating 1q32 with DR, 75 re-iterating the importance of this region. It is particularly interesting that neither GWAS investigating the retinopathy in type 1 and 2 DM found overlapping regions.…”
Section: Diabetic Retinopathy (Dr)supporting
confidence: 79%
“…Two of these genes (ARHGAP22 and PLXDC2) are involved in endothelial cell angiogenesis. They also confirmed the results of a previous genomewide linkage study associating 1q32 with DR, 75 re-iterating the importance of this region. It is particularly interesting that neither GWAS investigating the retinopathy in type 1 and 2 DM found overlapping regions.…”
Section: Diabetic Retinopathy (Dr)supporting
confidence: 79%
“…A number of studies have performed genome-wide linkage analysis in sibships, with inconsistent findings 321;322 . One study found evidence of linkage on chromosome 1p 321 , and another (in Pima Indians) found linkage on chromosomes 3 and 9 323 . To date, the majority of candidate genes studied have exhibited only a weak or no association with DR.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…Interestingly, there is a higher concordance of DR in T2D monozygotic twins (95%) than in T1D monozygotic twins (68%), suggesting that in T1D the initiation and development of its complications are less dependent on genetic factors than in T2D [11]. Additional family studies have shown that, depending on the DR phenotype and the ethnic population examined, siblings and relatives of diabetic patients with DR have approximately a 2-to 4-fold risk of developing the complication compared with relatives of diabetic patients without DR complication [5,[13][14][15][16][17][18]. The degree of familial aggregation is greater for more severe forms of retinopathy.…”
Section: Heritability and Linkage Studiesmentioning
confidence: 99%
“…A subsequent genome-wide linkage analysis in this population found stronger evidence for linkage on chromosome 1p with LOD scores of 2.58 and 3.1 for single-point and multipoint analyses, respectively [14]. Another genomewide linkage scan for genes contributing to DR, using 794 diabetes participants from 393 MexicanAmerican families in Starr County, Texas, having at least two diabetic siblings, revealed only suggestive evidence of linkage with retinopathy on chromosomes 3 and 12 [20].…”
Section: Heritability and Linkage Studiesmentioning
confidence: 99%
See 1 more Smart Citation